Hubungan Kadar Hemoglobin Dengan Siklus Menstruasi Remaja Putri - Juli Evianna Br Purba; Miftahul Jannah (Lembaga Pengembangan Kinerja Dosen, 2023)
value = 0.000 or valuer rAdolescence is a period of transition between childhood into adulthood, problem that often occurs in adolescence are less nutrition resulted in malnourished. Hb is a quantitative indicator to determine iron deficiency with the most severe level. Menstruation adalahperdarahan derived from this research uterus.Jenis Praeksperimen with the design of